2014
DOI: 10.3390/rs6042782
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Approach to Map the History of Forest Disturbance from Insect Mortality and Harvest with Landsat Time-Series Data

Abstract: Forests contain a majority of the aboveground carbon (C) found in ecosystems, and understanding biomass lost from disturbance is essential to improve our C-cycle knowledge. Our study region in the Wisconsin and Minnesota Laurentian Forest had a strong decline in Normalized Difference Vegetation Index (NDVI) from 1982 to 2007, observed with the National Ocean and Atmospheric Administration's (NOAA) series of Advanced Very High Resolution Radiometer (AVHRR). To understand the potential role of disturbances in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…However, there is consensus that aerial surveys are not directly suitable as reference data for calibrating or validating remote sensing insect damage maps (de Beurs and Townsend 2008;Neigh et al 2014). Aerial survey maps are inconsistent in assigning levels of forest damage, incomplete in spatial coverage, subjective in its derivation, and are prone to overestimating damage within delineated areas (MacLean and MacKinnon 1996;Johnson and Ross 2008).…”
Section: Validating Aerial Survey Mapsmentioning
confidence: 99%
“…However, there is consensus that aerial surveys are not directly suitable as reference data for calibrating or validating remote sensing insect damage maps (de Beurs and Townsend 2008;Neigh et al 2014). Aerial survey maps are inconsistent in assigning levels of forest damage, incomplete in spatial coverage, subjective in its derivation, and are prone to overestimating damage within delineated areas (MacLean and MacKinnon 1996;Johnson and Ross 2008).…”
Section: Validating Aerial Survey Mapsmentioning
confidence: 99%
“…Land cover conversion often exhibits a strong contrast between remotely-sensed images at two or more time points. However, stress-induced changes within the same cover type (e.g., forest degradation) do not necessarily have apparent signatures in the short term, but may show trends over a long time span [73]. Hence, it has been suggested that to detect forest degradation, land cover should be characterized as continuous biophysical variables, and the method should be flexible to capture trends at the inter-annual scales [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study has observed multiple disturbances for the entire 30+ year AVHRR record with trend changes in vegetation productivity [42]. The use of Landsat and ancillary data to identify disturbance type in conjunction with the coarse resolution AVHRR data have also shown promise [24,43]. Disturbance information could enable more advanced terrestrial C-cycle models to capture these C-cycle dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…We previously developed an automated procedure to capture harvest and insect outbreaks in the Laurentian forests of Wisconsin and Minnesota. This automated approach had 0.72 user's and 0.63 producer's accuracy for capturing insect mortality events, but had limited accuracy (0.56 user's and 0.36 producer's) in capturing insect outbreak that did not cause mortality, because of the temporally sparse Landsat Time Series Stacks (LTSS) [24]. In this study, we use a more robust time series that had limited phenology variability and a nearly complete annual anniversary record to evaluate the accuracy of this approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation